Potentiality of Steric and Compression Effect in Conformational Analysis: A 13C NMR Study - Verma, Mridula; M. Verma, Shiva (Asian Journal of Chemistry, 2010)
Conformational analysis by 13C NMR spectroscopy about Nsp2 − Csp2 bond in endo/exo isomeric systems of bicyclo-5- heptene-2,3-N-aryl dicarboximides have demonstrated that the steric and compression effect of the non-planar cage is quite diagnostic in the study of rotational processes. In cases of exo-N-aryl imides where, 1H NMR is not very sensitive, 13C NMR provides conclusive evidence about the rotational mode of the phenyl ring about the N-C bond.